Synthetic bPNAs as allosteric triggers of hammerhead ribozyme catalysis - Liang, Yufeng (Methods Enzymol, 2019)
The biochemistry and structural biology of the hammerhead ribozyme (HHR) have been well elucidated. The secondary and tertiary structural elements that enable sugar–phosphate bond scission to be catalyzed by this RNA are clearly understood. We have taken advantage of this knowledge base to test the extent to which synthetic molecules, may be used to trigger structure in secondary structure and tertiary interactions and thereby control HHR catalysis. These molecules belong to a family of molecules we generally call “bPNAs” based on our work on bifacial peptide nucleic acid (bPNA). This family of molecules displays the “bifacial” heterocycle melamine, which acts as a base-triple upon capturing two equivalents of thymine or uracil. Loosely structured internal oligouridylate bulges of 4–20 nucleotides can be restructured as triplex hybrid stems upon binding bPNAs. As such, a duplex stem element can be replaced with a bPNA triplex hybrid stem; similarly, a tertiary loop–stem interaction can be replaced with a loop–bPNA–stem complex. The ability to control RNA structure–function facilitates elucidation of these critical aspects of RNA recognition. In this chapter, we discuss how bPNAs are prepared and applied to study structure–function turn on in the hammerhead ribozyme system.